(untitled) (Research, Society and Development, 2022)
The present study aimed to detect the types and concentration of pesticides in the surface water of a dam located in an agricultural region, and relate them to aquatic bacterial density. 1L of water were collected six times, three in the dry season (D1, D2 and D3) and three in the rainy season (R1, R2 and R3). The pesticide analysis was performed using CG/MS. The bacterial density was analyzed by means of CFU counting. The most abundant colonies that were cultivated in all studied samples were isolated and identified by molecular methods. The bacterial density had a significant difference between the rainy and dry seasons. In the dry season, the average bacterial density (5.69x105±2.86 x105 UFC mL-1) was higher than in the rainy season (2.31x105±1.73 x105 UFC mL-1). In the dry season, lambda cyhalothrin (0.3 µg L -1) and endrin (0.23 µg L -1) were found in D1 collection and endosulfan sulfate in D1 and D2 (0.05 - 0.27 µg L -1). In the rainy season, DEA (0.02 - 0.09 µg L-1) and atrazine (0.02 - 0.06 µg L -1) were detected in all collections, metalachlor (0.2 µg L -1), chlorpyrifos (0.2 µg L -1) in R1 and R2 and endosulfan sulfate (0.1 µg L -1) in R1. In the dry season, the bacterial density in R1 was significantly lower than R2 and R3. High correlation among those pesticides and the bacterial density was observed. Endrin, lambda cyhalothrin and endosulfan sulphate are toxic and persistent pesticides, and may therefore have influenced the decrease in aquatic bacterial density. Molecular analyzes identified the bacterium Bacillus weihenstephanensis, known to be present in environments contaminated by pesticides and for its biodegradable potential.